Performance Study Of Carbon-Clad Zirconia Stationary Phase In High Temperature Reversed-Phase High Performance Liquid Chromatography - Sanagi, Mohd. Marsin; See, Hong Heng; Francis, Jaclyn Ann (Penerbit UTM Press, 2005)
The performance of carbon-clad zirconia (CCZ) stationary phase was evaluated for the separations of test compounds (benzaldehyde, benzamide, nitrobenzene, and toluene) and alkyl aryl ketones (acetophenone, propiophenone, butyrophenone and valerophenone) at high temperature (100˚C-160˚C) in reversed-phase high performance liquid chromatography (RP-HPLC) using low compositions of organic modifier and 100% pure water as eluent. Improved separation mechanism and faster analysis time were achieved during high operating temperatures. Van’t Hoff plots were linear for the investigated CCZ column, which showed that over the temperature range, no changes occurred in the retention mechanism. The use of alkyl aryl ketone homologs as a retention index scale in high temperature RP-HPLC was investigated. Although the retention factors of the test compounds were greatly affected by increasing the column temperature, there were only slight variations in their respective retention index values.